Biosynthesis of Silver Nanoparticles and Their Antibacterial Activity Against Urinary Tract Infection Bacteria - Fradi, Ahmed Jassim; Al-Bahrani, Rusol M. (Iraqi Journal of Science, 2026)
The rising use of antibiotics, particularly in developing nations, has made bacteria more skilled at creating resistance mechanisms, which has led to high infection and mortality rates.  The World Health Organization states that one of the biggest risks to human health is antibiotic resistance, which ranks third in terms of causes of mortality after cardiovascular disease.  The investigation and application of plant chemicals as natural antibiotics have continued in recent decades. Green synthesis of silver nanoparticles was carried out using volatile oils extracted from Citrus aurantium peels as a reducing agent. The particles were characterized by UV-Vis spectroscopy, FTIR, AFM, and colorimetric analysis. Results revealed that the size of the synthesized silver nanoparticles was 74.8 nm. particles irregular shapes and exhibited antimicrobial activity against antibiotic-resistant pathogens such as Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Enterococcus faecalis, causing urinary tract infections (UTIs). The agar well diffusion method evaluated the effect of the synthesized silver nanoparticles at three concentrations of 25%, 50%, and 75%, respectively, against pathogenic bacteria. The results showed significant variations between the concentrations and bacteria. The 75% concentration showed the highest effect on all bacteria compared to other concentrations, and S. aureus was the most sensitive, with an inhibition zone of 15.583 mm, while E. faecalis was less affected, with an inhibition zone of 10.167 mm, and there was no significant difference with E. coli, with an inhibition diameter of 10.583 mm. The results obtained indicated that the manufactured silver nanoparticles will pave the way for successful and environmentally friendly treatment methods against pathogens that cause urinary tract infections. In addition, industrial waste can be used to make important treatments.